Quality of focused thoracic ultrasound performed by emergency medical technicians and paramedics in a prehospital setting: a feasibility study - Pia Iben Pietersen (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2021)
Abstract Background In a prehospital setting, the severity of respiratory symptoms in patients calling for an ambulance differ. The initial evaluation, diagnosing, and thereby management can be challenging because respiratory symptoms can be caused by disease in many organs. Ultrasound examinations can contribute with important information and support the clinical decision-making. However, ultrasound is user-dependent and requires sufficient knowledge and training. The aim of this study was to explore the quality of thoracic ultrasound examinations performed on patients by emergency medical technicians and paramedics in a prehospital, clinical setting. Methods From November 2018 – April 2020, Danish emergency medical technicians and paramedics (n = 100) performed thoracic ultrasound examinations on patients with respiratory symptoms using a portable ultrasound device. The ultrasound examinations were stored and retrospectively assessed by a reviewer blinded to the patients’ symptoms and history, as well as the emergency medical technicians’ and paramedics’ findings. The image quality was scored from 1 to 5. The findings determined by the reviewer was then correlated with a questionnaire filled out by the emergency medical technicians and paramedics regarding ultrasonic findings and potential change in treatment or management of the patient. The agreement in percentage and as Cohen’s kappa was explored. Results A total of 590 ultrasound examinations were assessed, resulting in a median image quality score of 3 (IQ1 = 4, IQ3 = 3). The overall agreement in percentage between the emergency medical technicians and paramedics and reviewer was high (87.7% for a normal scan, 89.9% for interstitial syndrome, 97.3% for possible pneumothorax, and 96.3% for pleural effusion). Cohen’s kappa varied from 0.01 for possible pneumothorax to 0.69 for pleural effusion. Based on the questionnaires (n = 406), the ultrasound examination entailed a change in treatment or visitation in 48 cases (11.7%) which in this study population encompasses a number-needed-to-scan of 8.5. Conclusion Emergency medical technicians and paramedics perform focused thoracic ultrasound examinations with adequate image quality sufficient to determine if pathology is present or not. The emergency medical technicians’ and paramedics’ assessment correlates to some extent with an experienced reviewer and their findings are most reliable for the inclusion of a normal scan or inclusion of pleural effusion. Implementation could possibly impact the number of patients receiving correct prehospital treatment and optimal choice of receiving facility.